The Relationship Among Financial Inclusion, Non-Performing Loans, and Economic Growth: Insights From OECD Countries - Zhang, Peng; Zhang, Mengxue; Zhou, Qiancheng; Zaidi, Syed Anees Haider (Frontiers in Psychology, 2022)
This study implies finding the linkages among financial inclusion, non-performing loans (NPLs), and economic growth. The study uses large panel data of 21 Organization for Economic Corporation and Development (OECD) countries for the dynamic panel estimation by using the Driscoll-Kraay standard errors with fixed effect. The results of the dynamic panel estimation technique revealed the existence of a long-run relationship among financial inclusion, NPLs, and economic growth. Financial inclusion contributes positively to economic growth by reducing NPLs. Furthermore, NPLs negatively impact financial inclusion as well as economic growth. The study presents important policy recommendations to control NPLs and boost the level of financial inclusion in the selected economies.